Kramers–Henneberger atoms in flattened Gaussian beams - Ioksang Leung; Mingyu Zhu; Pingxiao Wang; Qi Wei (New Journal of Physics)
The dichotomy structure is one of the prominent features of Kramers–Henneberger (KH) atoms. Within a focused laser field, the wave function of KH atoms becomes polarized due to ponderomotive (PM) forces induced by light intensity gradients, leading to the disruption of the dichotomy structure. In a Gaussian-focused laser field, the PM forces are negligible only along the optical axis. To maintain the dichotomy structure of KH atoms over a broader area, we compared the result of flattened Gaussian laser beams with Gaussian-focused laser beams. By calculating the wave functions of ground KH state hydrogen atoms at various radial and angular locations in the laser focusing plane, it was demonstrated that under suitable laser parameters, the dichotomy structure can be fully or partially preserved in flattened Gaussian laser beams. Through the dichotomy structure of KH atoms, we can verify the existence of KH atoms using interference fringes of multi-photon ionization signals.